Ahmīyat-i tārīkhī-i dūstī-i Afghān-Shūravī barā-yi difāʻ az dast-i āvardʹhā-yi Inqilāb-i S̲awr - Rūdvāl, Muḥammad Hāshim (Maṭbaʻah-ʼi Difāʻ-i Millī, 1980)
On the importance of Afghanistan and Soviet Union friendship; chifly after the S̲awr Inqilāb in Afghanistan.